The Role of Empathy in Developing Professional Identity of would-be Economists in the home Reading Classroom - M. V. Grineva (Vestnik MGIMO-Universiteta)
Nowadays the growing professional orientation of all the aspects of foreign language teaching is widely recognized as one of the major trends in the process of enhancing foreign languages curriculum at higher education institutions which specialize in training non-linguistic students majoring in various fields of international relations. Professionally oriented foreign language teaching implies using the foreign language classroom as a source of forming a wide range of professionally meaningful competences (both linguistic and non-linguistic) of would-be specialists along with developing their sense of professional identity. Despite the fact that professional identity - usually interpreted as individuals' perception of themselves as members of a certain profession - is the culmination of a long process of professional development, its cultivation with future specialists should be seen as a priority as early as at a higher education level - a college or university. Referring to psychological research, the author states that emotional factors play a decisive role in shaping professional identity at early stages of a person's professional development. It reveals the importance of analyzing the potential of literary texts in a foreign language in terms of their ability to contribute to developing prospective specialists' professional identity, as such texts represent a valuable text material which provokes readers' powerful emotional response and thus triggers empathy. The novel "The Firm" byJ. Grisham and "The Headhunter" byj. Mead were selected by the author for the home reading classroom with would-be economists, as coupled with a competence-based learning aid they allow teachers to create a unique discourse, which facilitates the process of developing students' professional competences and their professional identity. Along with their clear professional content, they appeal to students, as the problems raised in them are relevant to those of young readers. Such emotional contact provokes empathy, or a feeling of compassion and sympathy, which contributes to tackling the above pedagogical tasks. According to the author, empathy as a means of developing professional identity is realized through students' analyzing and assessing the professional behaviour of literary characters and their identifying themselves with protagonists or distancing from antagonists guided by professional criteria. It is essential that reading the above novels enrich would-be economists with the knowledge and experience, though non-empiric, of various business situations. The author concludes that such information about the profession in question is likely to prove valuable, as it "has been digested" by students by identifying their moral and professional attitude to it.